A rare of Turner syndrome with a special karyotype: a case report - W.D. Huang; M. Pang; Q.Z. Zhao; X.P. Wang; J. Wang; Y. Mao; L.Y. Kong; B. Liang (Clinical and Experimental Obstetrics & Gynecology)
Turner syndrome (TS) is a gonadal dysgenesis caused by absence or structural abnormalities of sex chromosome. Isochromosome Mosaic TS is a structurally abnormal X chromosome consisting of either two short or two long arms, with only an 8-9% prevalence among women with TS based on international studies. The present report describes a 30-year-old female with isochromosome mosaic karyotype TS. The patient had no menarche so far. G-banding chromosome analysis indicated mosaic 45, X[3]/46, X, i(X) (q10)[79]/47, X, i(X)(q10), i(X)(q10), i(X)(q10)[3]/49, X, i(X)(q10), i(X)(q10), i(X)(q10), i(X)(q10)[79]. Both clinical and cytogenetic investigations proved this patient to be a special isochromosome Xq Mosaic TS with autoimmune hypothyroidism and hyperlipidemia.